About inter-university cooperation in culturological studies - A. I. Gelyaeva; M. CH. Kremshokalova (Высшее образование в России)
The paper is focused on the significance of cross-cultural research in the context of formation of the Russian identity and the special role of regional higher school science in this field. It points the apparent inconsistency of the existing forms and levels of inter-university cooperation of humanitarian studies with the challenges of time and demands of Russia’s development towards consolidation of the society and cultural and technological ascension.